"System aisa hi hai" – exploring local researchers' perspective on barriers toward conducting locally relevant disaster research. Issue 2 (26th January 2022) - Das, Manomita
Abstract : Purpose: The paper explores why local disaster scholars often fail to put the needs of local people at the centre of their research. Specifically, it explores two questions: (1) why local concerns are often not reflected in the research agenda? And (2) why we are falling behind in generating locally applicable disaster knowledge? The paper engages with the experiences of local disaster researchers to answer the research questions. Design/methodology/approach: A qualitative approach was undertaken to conduct the study. In total, 15 in-depth interviews were conducted with practitioners and academics working in the domain of disaster studies in different regions of India. Criterion sampling was employed to recruit the participants. An interview guide with open ended questions was used to conduct the interviews. The data were thematically analysed utilizing qualitative data analysis software to arrive at the findings. Findings: The participants identified three potential reasons behind the lack of locally relevant disaster research. First, the existing concepts and terminologies which guide disaster research are often inadequate to represent the local reality. Second, "foreign" funders and policymakers often influence the agenda and emphasis of the research which creates barriers in developing research agenda relevant to the local needs. The time-bound project format of research is often problematic. It resembles looking at the community through a peephole which hardly gives the whole picture. Third, resource constraints also create substantial hindrances in conducting locally relevant research. Research limitations/implications: The sample only included participants who believed that disaster research is often not relevant locally in India. Participants having different standpoints on the issue were not included which remains as a limitation of the study. Practical implications: The research highlights the challenges that local researchers face while conducting locally relevant research and how they can be overcome. The author expects that the findings of the research will help in challenging and transforming established practices in disaster studies and bridging the gap between disaster research and vulnerable people. Originality/value: This paper is valuable because it documents the perspectives of local researchers on the barriers that need to be overcome to produce locally relevant disaster research.